Desempenho térmico e eficiência energética em edifício de escritório : análise do uso de fachadas de vidro diretamente expostas à radiação solar na cidade de Cuiabá-MT - Saldanha, Alessandra Migliorini (2012)
The thermal behavior of an edification refers to the physical process of energy transference between the building and its surroundings. This property depends on factors such as implantation, orientation, used materials and constructive components, which, therefore, must be properly appraised and defined for each climatic condition. The building, through its wrappers (walls, floor, covering and openings) and the elements of the environment, it acts as a control mechanism of the climatic condition effects, forasmuch, it must be projected to provide comfort and energetic efficiency. Among the constructive elements, the glasses present the highest possibilities of thermal gain to the inside environments because of their transparency to the solar radiation, which allows the transference of a big part of this energy to the environment. In this context, this work presents a study of case through measurements in loco about the thermal performance and the energetic efficiency in an office building with glass façade directly exposed to the sun radiation, in the city of Cuiabá – MT, and also, evaluates the influence of construction parameters in the intake of energy through computer simulations using the program EnergyPlus. Cuiabá occupies a geographical position that grants tropical weather conditions, with a seasonal rhythm with two well-marked periods: hot- dry and hot-wet. The architectonic party chosen adopts the use of big glazed areas without any kind of protection, characteristic of the international patterns. To accomplish the studies, the methodology adopted is directed to the evaluation of the buildings’ thermal performance, glass’s thermal performance, users’ thermal comfort and, lastly, the energetic efficiency through computer simulation. The obtained results show that the edification presents thermal underachieve to both considered periods and that the heat gain of the glass was more significant to the hot-dry period. In the scope of thermal comfort of the user, it was verified that to both periods, it’s only possible to achieve the levels established by ISO 7730 (2005) when there is contribution of mechanic air conditioner. About the simulation, it was possible to testify that beyond the inadequate thermal performance, the edification isn’t energetically efficient either, mainly about the heat gain through the edification.